Estudo comparativo da corte e cópula de duas espécies de aranhas da família Dipluridae (Araneae, Mygalomorphae) - Ghirotto, Victor Morais [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The family Dipluridae (Araneae, Mygalomorphae) is represented by small to medium spiders, spinners of sheet or funnel webs. In its current composition, it is a polyphyletic group, including the subfamilies Ischnothelinae (present in Africa, Central and South America and India), Euagrinae (Africa, Oceania, North and Central America, Indochina and Central Asia), Masteriinae (Oceania, Central and South America) and Diplurinae (South America). The sexual behavior of these spiders is poorly known, and studies exist only for seven species, Microhexura montivaga Crosby & Bishop, 1925 (Euagrinae), three Euagrus spp. Ausserer, 1875 (Euagrinae), Australothele jamiesoni Raven, 1984 (Euagrinae), Phyxioschema suthepium Raven & Schwendinger, 1989 (Euagrinae) and Thelechoris striatipes (Simon 1889) (Ischnothelinae). In the present work, the courtship and mating behavior, under laboratory conditions, of Diplura macrura C. L. Koch 1841 (Diplurinae) and Ischnothele annulata Tullgren 1905 (Ischnothelinae) are detailed described. Moreover, these behaviors are analyzed and compared through a phylogenetic scope, both in a context of the Dipluridae family and of the Mygalomorphae infraorder. Five new sexual behavioral categories for the family are recorded, and two unique behaviors were observed and described for the first time. These descriptions constitute the first of this kind for the subfamily Diplurinae and for Neotropical species of Dipluridae. The courtship in the two species is initiated after male contacting the female's web. The reproductive behavior in D. macrura involves, in males, the following categories: body vibration, palpal drumming, brushing, clasping, palpal boxing, hugging and alternating insertions of palps. In females, body vibration, leg tapping, and catalepsis were recorded. In I. annulata it involves, in the males, body vibration, palpal drumming, brushing, post-brushing, clasping, palpal boxing, insertion lifting and alternating insertions...

A família Dipluridae (Araneae, Mygalomorphae) está representada por aranhas de pequeno a médio porte, construtoras de teias de lençol ou funil. Em sua composição atual, é um grupo polifilético, incluindo as subfamílias Ischnothelinae (presente na África, América Central e do Sul e Índia), Euagrinae (África, Oceania, América do Norte e Central, Indochina e Ásia Central), Masteriinae (Oceania, América Central e do Sul) e Diplurinae (América do Sul). O comportamento sexual destas aranhas é pouco conhecido, existindo estudos apenas para sete espécies, Microhexura montivaga Crosby & Bishop, 1925 (Euagrinae), três Euagrus spp. Ausserer, 1875 (Euagrinae), Australothele jamiesoni Raven, 1984 (Euagrinae), Phyxioschema suthepium Raven & Schwendinger, 1989 (Euagrinae) e Thelechoris striatipes (Simon 1889) (Ischnothelinae). No presente trabalho, são descritos detalhadamente a corte e cópula, em condições laboratoriais, de Diplura macrura C. L. Koch 1841 (Diplurinae) e Ischnothele annulata Tullgren 1905 (Ischnothelinae). Ainda, estes comportamentos são analisados e comparados sob escopo filogenético, tanto num contexto da família Dipluridae como da infraordem Mygalomorphae. Cinco novas categorias comportamentais sexuais para a família são registradas, e dois comportamentos únicos foram observados e descritos pela primeira vez. Estas descrições constituem a primeira deste tipo para a subfamília Diplurinae e para espécies neotropicais de Dipluridae. A corte nas duas espécies é iniciada após o macho contactar a teia da fêmea. O comportamento reprodutivo em D. macrura envolve, nos machos, as seguintes categorias: body vibration, palpal drumming, brushing, clasping, palpal boxing, hugging e inserções alternadas dos palpos. Nas fêmeas, foram registradas: body vibration, leg tapping, e catalepsis. Em I. annulata envolve, nos machos, body vibration, palpal drumming, brushing, post-brushing, clasping, palpal boxing, insertion...
Keywords: Aranha; Copulação; Filogenia; Animais - Comportamento